2011
DOI: 10.1007/s13197-011-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vacuum packaging on seed quality and mineral contents in chilli (Capsicum annuum L.)

Abstract: Studies were carried out to find out the influence of vacuum packaging on physical parameters of whole chilli and biochemical constituents in chilli seeds. Chilli fruits were stored in vacuum packed and jute bags stored at room temperature (25±2°C), cold storage (4±1°C) under both light and dark conditions for a period of 24 months. At the end of the storage period, seeds were separated from fruits and various parameters viz., moisture content, capsaicin content, ascorbic acid, carbohydrates, protein and miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…Similar trend also was found by Oluwatosin et al, (2016) for Moringa oleifera kernels and by Deepa et al, (2013) for stored chili seeds under vacuum. (Table 4).…”
Section: Effect Of Storage Period At Different Storage Conditions On supporting
confidence: 89%
See 1 more Smart Citation
“…Similar trend also was found by Oluwatosin et al, (2016) for Moringa oleifera kernels and by Deepa et al, (2013) for stored chili seeds under vacuum. (Table 4).…”
Section: Effect Of Storage Period At Different Storage Conditions On supporting
confidence: 89%
“…It could be due to property of protein chains, which form loose mesh with increase in moisture content, when sample stored at room temperature in control conditions and under vacuum and modified atmosphere storage, it was found in decreased state. This trend was also found by Deepa et al, (2013) for chili seeds stored under vacuum.…”
Section: Effect Of Storage Period At Different Storage Conditions On supporting
confidence: 76%
“…The world spice production statistics records a bulk of 86% by volume, making the country the largest producer of spices, in addition to it being the largest consumer and exporter of spices in the global context [3,4]. Chili has high medicinal value due to the abundance of availability of carotenoids, capsaicinoids [5], oleoresins, and mineral content [6]. Most of the studies have demonstrated that consumption of chili rich diets, increases in energy expenditure and oxidation of fat, and also it helps in the curing of many diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…High-quality seeds generally determine the output and quality of agricultural production, and are also the basis of maintaining high energy and vigor during the period of storage to guarantee their application value (Deepa et al, 2013;Hampton et al, 2013). However, deterioration occurs in the process of seeds storage, which causes a drop of seed vigor, poor seedling emergence and bad influence on intracellular physiological reactions (McDonald, 1999;Kapoor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%